Damage effects and mechanism of electron irradiation on flexible solar cell coverglass-pseudomorphic glass. (August 2022) - Zhao, Huiyang; Wang, Hao; Sun, Chengyue; Ju, Dandan; Yu, Hui; Cui, Xinyu; Guo, Hongliang; Wu, Yiyong; Kobykhno, Ilya A.; Tolochko, Oleg V.
Abstract: Flexibility, light weight and high reliability are the development themes of space solar cells. Pseudomorphic Glass (PMG) is considered as a novel feasible flexible encapsulation solution for solar cells. In this paper, the degeneration and damage mechanism of PMG morphology, optical and mechanical properties under 170 keV electron irradiation were studied. The change of PMG surface wrinkles structure under the fluence of 1 × 10 13 cm −2 to 1 × 10 16 cm −2 was observed by Scanning Electron Microscope (SEM). After electron irradiation, the defect optical absorption peak intensity of PMG was significantly lower than that of room-temperature-vulcanized silicon rubber (RTV) sheet, showing obviously excellent electron irradiation stability. The transmittance of PMG at the wavelength greater than 500 nm increased significantly while the RTV sheet remained unchanged when the fluence reached 1 × 10 16 cm −2, which was mainly caused by the decrease of scattering loss at the bead-adhesive interface. Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) indicated that "organic silicon" was transformed into "inorganic silicon" and Si–OH groups were formed during electron irradiation. Furthermore, the stress-strain test showed that the elongation at break (Eb ) decreased from 113% to 9% and the modulus of elasticity increased from 2.5 MPa to 9 MPa. Highlights: The optical and mechanical properties of PMG before and after electron irradiation were studied systematically. The decrease of scattering loss at bead-adhesive interface leads to the increase of PMG transmittance. The adhesive was transformed from "organic silicon" to "inorganic silicon". The elongation at break (Eb ) decreased from 113% to 9% and the modulus of elasticity increased from 2.5 MPa to 9 MPa.